Re-imagining the International Monetary Fund. (March 2014) - Sinha, Manisha
The admission by the International Monetary Fund (IMF) that it did not accurately estimate the damage that austerity will do to the Greek economy is yet another failure of the world body. It has admitted making similar mistakes in the past in handling economic crises in Mexico, Russia and Argentina. What was the exact nature of the Greek financial crisis? And how did the IMF handle this crisis? What were the Fund's follies in its handling of the Greek crisis? Is there a pattern in the follies of the Fund in handling economic crises? If yes, then what does it tell us about the IMF and its governance of the world economy? This article seeks to answer these questions in the wake of long-pending reforms of the Fund's governing structure and voting rights. Obviously, there is a need for more than just 'fine-tuning' of the Fund's lending policies. Reforms such as expansion of the governing committee and increasing the quota share of developing countries are crucial for 're-imagining' a stronger and more effective IMF that is more in tune with the changing global order of the twenty-first century. This article will take stock of the IMF quota and governance reforms initiated by the Fund in 2010 and review some other reform proposals that reflect the significant shifts in global economic power in the twenty-first century.